How Microsolvation Affects the Balance of Atomic Level Mechanism in Substitution and Elimination Reactions: Insights into the Role of Solvent Molecules in Inducing Mechanistic Transitions - Gang Fu; Hongyi Wang; Wenqing Zhen; Xin Zhou; Li Yang; Jiaxu Zhang (Molecules)
Solvents play a crucial role in ion–molecule reactions and have been used to control the outcome effectively. However, little is known about how solvent molecules affect atomic-level mechanisms. Therefore, we executed direct dynamics simulations of the HO−(H2Ow) + CH3CH2Br system to elucidate the dynamics behavior of chemical reactions in a microsolvated environment and compared them with previous gas-phase data. Our results show that the presence of a single water solvent molecule significantly suppresses the direct mechanism, reducing its ratio from 0.62 to 0.18, thereby promoting the indirect mechanism. Spatial effects and prolonged ion–molecule collisions combine to drive this mechanism shift. Among them, water molecules impede the reactive collisions of HO− and CH3CH2Br, while at the same time, the attractive interaction of hydrogen bonds between ions and molecules produces long-lived intermediates that favor the indirect mechanism. On the other hand, microsolvation also affects the reaction preference of the SN2 and E2 channels, which is more conducive to stabilizing the transition state of the SN2 channel due to the difference in solute–solvent interactions, thus increasing the competitiveness of this pathway. These results emphasize the profound influence of solvent molecules in regulating reaction selectivity and underlying microscopic mechanisms in more complex systems.